POTENSI ANTIINFLAMASI EKSTRAK TERPURIFIKASI HERBA SAMBILOTO ANDROGRAPHIS PANICULATA) MELALUI INHIBISI ENZIM SIKLOOKSIGENASE - Irfan Muris Setiawan; Arief Rahman Hakim (Fakultas Farmasi Universitas Setia Budi, 2025)
Inflammation is a natural respond of the body to harmful stimuli from external environment. However, persistent and prolonged inflammation has been associated with the development of various chronic diseases. The objective of this study is to investigate the cyclooxygenase (COX) inhibitory activity of purified extract of Andrographis paniculata (sambiloto) herb. The extraction process was performed through maceration using ethanol 90 %, followed by fractionation with n-hexane and ethyl acetate solvent. This procedure yielded a purified extract of sambiloto herb 2.3 % relative to the dry weight of herb. The COX inhibition assay demonstrated IC50 value of 563.2 µg/mL and 5097.4 µg/mL for COX-1 and COX-2 respectively. These results indicate that purified extract of sambiloto herb exhibits greater inhibition selectivity towards COX-1 compared to COX-2.